Advancing the Empirical Study of Performance Management: What We Learned From the Program Assessment Rating Tool. (September 2013) - Moynihan, Donald P.
Interest in performance management has never been higher. But what does actual research on this topic tell us about the effects of performance management, reform efforts, and governance more generally? Historically, the answer often seemed to be that such reforms did not work very well. This article focuses on a recent chapter in the history of performance management at the U.S. federal government, the Program Assessment Rating Tool (PART). PART was created by the George W. Bush administration, and ended by the Obama White House. PART, like many management initiatives, came and went. What distinguishes it, however, is the quality and breadth of the research it prompted—research that has increased our knowledge of performance management and reform implementation as well as a whole host of fundamental governance phenomena such as political ideology, administrative burden, performance information use, leadership commitment, and goal ambiguity.